2022
DOI: 10.3390/f13101586
|View full text |Cite
|
Sign up to set email alerts
|

Mites Associated with the European Spruce Bark Beetle Ips typographus (Linnaeus, 1758) in Europe, with New Evidence for the Fauna of Serbia

Abstract: Various biotic and abiotic factors are the cause of the decline of coniferous forests throughout Europe. Trees weakened by unfavorable weather conditions create an ideal environment for a possible outbreak of bark beetles. The damage caused by bark beetles costs billions of dollars worldwide every year. Extreme climate events are responsible for the enormous forest losses in Tara National Park in the last ten years, leading to a massive bark beetle infestation. The understanding of the diversity and role of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…The number of phoretic species found on the pinyon pine engraver, Ips confusus, in this study is typical for the number of beetles observed compared to other bark beetle species (Moser et al 2005, Pernek et al 2008, Milosavljević et al 2022. However the abundance of phoretic mites per beetle and percent beetles with mites was higher than most studies (Moser 1976, Pernek et al 2008, Cilbircioğlu et al 2021.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…The number of phoretic species found on the pinyon pine engraver, Ips confusus, in this study is typical for the number of beetles observed compared to other bark beetle species (Moser et al 2005, Pernek et al 2008, Milosavljević et al 2022. However the abundance of phoretic mites per beetle and percent beetles with mites was higher than most studies (Moser 1976, Pernek et al 2008, Cilbircioğlu et al 2021.…”
Section: Discussionsupporting
confidence: 40%
“…Dendrolaelaps quadrisetosimilis was found underneath elytra, which may provide protection from predators and mechanical removal during beetle tunneling and flight. Dendrolaelaps and Proctolaelaps lack specialized structures for phoretic dispersal, which may be why many Proctolaelaps were found in the gel capsule and Dendrolaelaps under the elytra (Knee et al 2012, Milosavljević et al 2022. Ereynetes propescutulis were found on various locations on the beetle and in the gel capsule, which may be due to a lack of specialized adaptations for phoresy in this species (Khaustov et al 2018).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation